The Influence of Self-Efficacy and Job Satisfaction on Employee Engagement Teachers of State Vocational High Schools in Depok - Iin Asikin; Burhan Burhan (Jurnal Ad'ministrare, 2021)
One of the competitiveness of vocational high school graduates depends on the quality of teachers who teach so that they  can improve the skills and insights of vocational high school students. For this reason, the government seeks to improve the quality, integrity, and innovation of vocational high school teachers so that graduates produced by vocational high schools can become ready to use workers and can reduce unemployment. The research aims to examine The effect of self-efficacy and job satisfaction on employee engagement teachers of state vocational high schools. This study uses a survey approach and quantitative method. Data collection in this study was conducted using a Likert scale questionnaire. Questionnaires are arranged based on indicators from research variables. The validity test was done by using the Pearson Product Moment formula, while the reliability test was done by using the Cronbach Alpha formula. The data analysis technique in this study used path analysis. Data from the research instruments were analyzed by descriptive statistics and inferential statistics. The result of the study reveals that Self-efficacy has a  direct effect on employee engagement; Job satisfaction has a direct effect on employee engagement teachers; and; Self-efficacy has a direct effect on job satisfaction